Florida Crop/Pest Management Profiles: Snap Beans - Wael M. Elwakil; Mark A. Mossler (EDIS)
In 2009-2010, Florida growers produced 193.2 million pounds of snap beans, with a value of $0.69 per pound and a total value of $135 million. Snap beans were planted on 36,400 acres, and 32,200 acres were harvested, yielding an average of 6,000 pounds per acre. This revised 18-page fact sheet was written by W.M. Elwakil and Mark A. Mossler, and published by the UF Department of Agronomy, October 2012.